Comparative evaluation of agar dilution and broth microdilution by commercial and in-house plates for Bacteroides fragilis group: An economical and expeditious approach for resource-limited settings. (October 2021) - Sood, Anshul; Angrup, Archana; Ray, Pallab; Bala, Kiran
Abstract: Objective: To compare the performance of agar dilution and broth microdilution by commercial and in-house prepared plates for the Bacteroides fragilis group. The cost analysis was performed to demonstrate that in-house prepared BMD plates were a suitable alternative to agar dilution given the high cost and low feasibility of incorporating commercial BMD plates in routine, particularly in the tertiary care institutes of many low- and middle-income countries. Methods: Thirty B. fragilis group isolates were tested against six antibiotics, frequently used as empirical therapy for anaerobic infections including metronidazole, clindamycin, imipenem, piperacillin-tazobactam, cefoxitin, and chloramphenicol. The running consumable expenditure for all methodologies was calculated. Results: The results demonstrated essential and categorical agreement of >90% for all antibiotics except cefoxitin, which showed <90% categorical agreement. No major or very major errors were observed. We observed a high agreement and strong concordance for MIC values between both methods and inter-rate reliability of >0.9 by Cohen's kappa analysis, indicating almost perfect agreement between both methods using either of the plates. In contrast to agar dilution, a 20.5 fold cost reduction was seen in BMD using in-house plates and a 5.8 fold reduction using commercial plates to test a single isolate. However, when testing 30 isolates concurrently the cost significantly increased for commercial BMD plates by 8.4 folds, and only 1.03 fold cost reduction was seen with in-house BMD plates. Conclusion: BMD gives comparable results to agar dilution and can be considered a method of choice to test a small number of samples. The technique is an economical option when plates are standardized in-house and could be employed for susceptibility testing of the B. fragilis group. Highlights: AMR is emerging in B. fragilis group, which demands a frequent and adequate AST. We demonstrated the feasibility of AD and BMD using in-house and commercial plates. AD is suitable for testing many isolates and uneconomical for a small number. BMD appears to be a cheaper and less laborious choice if prepared in-house. Our work may inspire resource-limited settings to integrate BMD in the routine AST.